The Importance of Nitrates in Coronary Heart Disease - Usmanovna, Begnaeva Mukhiba (American Journal of Bioscience and Clinical Integrity, 2025)
Nitrates have been used in cardiology since the end of the 19th century. Initially, they were used to relieve attacks of angina pectoris. Since the middle of the 20th century, when long-acting drugs appeared, they began to be prescribed for the prevention of angina attacks. Currently, there is a huge number of drugs from the nitrate group, related to various chemical substances and dosage forms, which makes it difficult for the doctor to choose the most optimal drug for a particular patient.